ENHANCING THE INTERACTIVITY AND ENGAGEMENT OF THE LEARNING PROCESS IN TEACHING RUSSIAN - Marufjon Ganiev (Scholars Digest Publishing, 2025)
The article examines the issues of enhancing the interactivity and engagement of the learning process in teaching the Russian language. The research results show that multimedia tools, online tests, virtual speaking clubs, and gamification elements play a crucial role in making the learning process more effective and engaging. When interactivity and student activity are harmoniously combined with the teacher’s guiding and supervisory role, language skills develop systematically, and students’ speech culture and creative thinking abilities are improved. The article also analyzes the pedagogical advantages of using innovative technologies in Russian language lessons and their practical application.
Keywords: Innovation, educational efficiency, innovative technology, information technology, speech culture, pedagogical mastery, interactivity of the learning process, pedagogical activity.